Certification is hard to get - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Emmanuel Antwi, General Secretary of the Ghana Organic Agriculture Network (PO Box 6342, Kumasi, Ghana), observes that 'the development of a local organic certificate programme (see main article, page 1) is an important step in promoting organic...